2020
DOI: 10.1038/s41419-020-02858-3
|View full text |Cite
|
Sign up to set email alerts
|

Mex3a interacts with LAMA2 to promote lung adenocarcinoma metastasis via PI3K/AKT pathway

Abstract: Lung adenocarcinoma (LUAD) is the main subtype of lung cancer. In this study, we found that RBP Mex3a was significantly upregulated in LUAD tissues and elevated Mex3a expression was associated with poor LUAD prognosis and metastasis. Furthermore, we demonstrated that Mex3a knockdown significantly inhibited LUAD cell migration and invasion in vitro and metastasis in nude mice. Transcriptome sequencing indicated that Mex3a affected gene expression linked to ECM-receptor interactions, including laminin subunit al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 37 publications
3
96
0
1
Order By: Relevance
“…However, in vitro and mouse xenograft analyses support a potential function of MEX3A in mesenchymal transition. Consistently, MEX3A knockdown studies revealed migratory potential by reducing CDH2, VIM, SNAI1/2 and increasing CDH1 protein levels, and additionally exhibited reduced lung metastasis [ 75 ]. This could be facilitated by an altered PTEN function due to K27-linked ubiquitination mediated by MEX3A, as proposed for MEX3C [ 26 ], but further mechanistic studies are necessary to exclude a transcriptional or post-transcriptional regulation of EMT processes.…”
Section: A Snapshot View Of Mex3a’s Disease Driving Potential In Cancermentioning
confidence: 80%
See 1 more Smart Citation
“…However, in vitro and mouse xenograft analyses support a potential function of MEX3A in mesenchymal transition. Consistently, MEX3A knockdown studies revealed migratory potential by reducing CDH2, VIM, SNAI1/2 and increasing CDH1 protein levels, and additionally exhibited reduced lung metastasis [ 75 ]. This could be facilitated by an altered PTEN function due to K27-linked ubiquitination mediated by MEX3A, as proposed for MEX3C [ 26 ], but further mechanistic studies are necessary to exclude a transcriptional or post-transcriptional regulation of EMT processes.…”
Section: A Snapshot View Of Mex3a’s Disease Driving Potential In Cancermentioning
confidence: 80%
“…This could be facilitated by an altered PTEN function due to K27-linked ubiquitination mediated by MEX3A, as proposed for MEX3C [ 26 ], but further mechanistic studies are necessary to exclude a transcriptional or post-transcriptional regulation of EMT processes. Along this line, several reports indicate a role of MEX3A in the activation of the PIK3CA/AKT signaling pathway [ 67 , 74 , 75 , 82 ] that is involved in the regulation of, e.g., proliferation, metabolism, transcriptional control or cell migration (for review see [ 83 ]). Accordingly, MEX3A induced migratory phenotypes, as well as pronounced mesenchymal expression patterns, could be mediated by the activation of the AKT pathway affecting inter alia SNAI1, SNAI2 and TWIST levels [ 84 ], which are the main transcriptional drivers of EMT.…”
Section: A Snapshot View Of Mex3a’s Disease Driving Potential In Cancermentioning
confidence: 99%
“…The KEGG pathway analysis was enriched by the DEmiRNA and DEmRNA. Phagosome, Human T-cell leukemia virus 1 infection, and ECM-receptor interaction were significantly enriched in the AD, which was closely associated with the immune microenvironment and the maintenance of cell structure and function [24,25]. The cell cycle and p53 signaling pathways were significantly enriched in the SC, which was closely connected to the basic biological processes and signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from cell lines and tissues using the RNeasy Mini kit (Qiagen GmbH). Related data were uploaded in the Gene Expression Omnibus (GEO) ( http://www.ncbi.nlm.nih.gov/geo ) dataset GSE140797 ( 19 ). The gene expression levels and clinical data of patients with LUAD from The Cancer Genome Atlas (TCGA) were downloaded from UCSC Xena Browser ( https://xenabrowser.net/ ).…”
Section: Methodsmentioning
confidence: 99%